The competency-based education and the curriculum design - Machado Ramírez, Dr. Cs. Evelio Felipe; de Oca Recio, Dr. C. Nancy Montes (Transformación, 2021)
Objective: This paper aims at disclosing the main problem competency-based education curricular design is currently facing. Methods: The researchers rely on a qualitative methodology for systematizing theory and practice. Results: The main finding is a body of requisites for competency-based education curricular design from the perspective of the historical and cultural approach. Conclusion: The study proves that prove that competency-based education curricular design demands a high specialized levels, a forecasting sense, creativity, innovation, researching experience, together with a personal commitment of designers to the graduates’ professional contextual environment.